Performance Analysis of the Covid-19 Staple Food Social Assistance Activities Carried Out by the Office of Social Affairs of Karanganyar Regency in 2020 and 2021 using the Value for Money, Justice, and Equality Concepts - Handayani Kusumawardhani; Sri Hantoro; Labbaika Dwi Ayu Rahmawati (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
This study aims at examining the performance of the Covid-19 staple food social assistance activities carried out by The Office of Social Affairs of Karanganyar Regency in 2020 and 2021 using the value for money (effectiveness, efficiency, and economic aspects), justice, and equality approaches. The results of this study have revealed that the Covid-19 staple food social assistance activities by the Office of Social Affairs of Karanganyar Regency in 2020 and 2021 are effective, efficient, fair, and equal. However, the economic aspect is not taken into account in this study. Based on the results of the study, the researchers propose some recommendations. The effectiveness and efficiency level should be maintained and improved. At the economic level, calculations should not be necessary because this level is not a top priority and can only be affected by limited resources. The justice and equality level should be maintained and increased.